Комплекс экспериментальных исследований электрических свойств горных пород в инертной среде - Кравчук, М.В.; Корчин, В.А.; Коболев, В.П.; Новик, Н.И. (Геофизический журнал, 2018)
Детально описано конструкцію і розглянуто апаратурно-методичні особливості розробленого і реалізованого в Інституті геофізики НАН України автоматизованого вимірювального комплексу, призначеного для дослідження електричних параметрів мінеральної речовини за температур до 1100 °С у кисневмісному та інертному середовищах. Наведено результати деяких експериментів, виконаних на етапі дослідних випробувань комплексу в температурному інтервалі від кімнатної до 700 °С. Досліджено та проаналізовано чинники, що впливають на характер отриманих температурно-частотних залежностей електричних параметрів зразків порід. Показано, що утворення оксидів у кисневмісному середовищі збільшує електричний опір. Різниця градієнта зміни величини r від температури, особливо в інтервалі 300.°500 °С, зумовлена тим, що електропровідність здійснюється в основному іонами домішок і дефектами кристалічної ґратки. За підвищення температури діелектрична проникність іонних кристалів зростає внаслідок ослаблення зв'язку між окремими іонами. Низькочастотна діелектрична проникність найчутливіша до деформаційних фазових переходів і є інформативнішим параметром, оскільки змінюється з найбільшим градієнтом. In the work presented, the construction and the hardware-methodological features of the automated measuring system developed and realized at the Institute of Geophysics of the National Academy of Sciences of Ukraine designed to study electrical parameters of the mineral substance at temperatures up to 1100 °C in oxygen-containing and inert media are described in detail. The results of some experiments performed at the stage of experimental tests of the complex in the temperature range from room temperature to 700 °C are shown. The factors influencing the character of the obtained temperature-frequency dependences of the electrical parameters of the investigated samples are considered and analyzed. It is shown that the formation of oxides in an oxygen-containing medium increases the electrical resistance. The difference in the gradient of the change in r from the temperature, especially in the range 300—500 °C, is due to the fact that the electrical conductivity is carried out mainly by impurity ions and crystal lattice defects. As the temperature is raised, the dielectric constant of ionic crystals increases, which is due to the weakening of the bond between the individual ions. Low-frequency permittivity is the most sensitive to deformation phase transitions and is a more informative parameter, since it varies with a larger gradient.